Clinical experience with a bioartificial liver in the treatment of severe liver failure. A phase I clinical trial. - Watanabe, F D (1997)
OBJECTIVE: The purpose of this study was to develop a bioartificial liver (BAL) to treat patients with severe liver failure until they can be either transplanted or recover spontaneously. SUMMARY BACKGROUND DATA: Severe acute liver failure is associated with high mortality. Liver transplantation has emerged as an effective therapy for patients who did not respond to standard management. However, because of the donor organ shortage and urgent need for transplantation, many patients die before they can be transplanted and others do not survive after transplantation, primarily because of intracranial hypertension. METHODS: Three groups of patients with severe acute liver failure were treated with the BAL. In group 1 (n = 18) were patients with fulminant hepatic failure (FHF), in group 2 (n = 3) were patients with primary nonfunction (PNF) of a transplanted liver, and in group 3 (n = 10) were patients with acute exacerbation of chronic liver disease. Patients in groups 1 and 2 were candidates for transplantation at the time they entered the study, whereas patients in group 3 were not. RESULTS: In group 1, 16 patients were "bridged" successfully to transplantation, 1 patient was bridged to recovery without a transplant, and 1 patient died because of concomitant severe pancreatitis. In group 2, all patients were bridged successfully to retransplantation. In group 3, two patients were supported to recovery and successful transplants at later dates; the other eight patients, although supported temporarily with the BAL, later died because they were not candidates for transplantation. CONCLUSIONS: The authors' clinical experience with the BAL has yielded encouraging results. A randomized, controlled, prospective trial (phase II-III) is being initiated to determine the efficacy of the system.